Avaliação do pH e da condutividade elétrica do substrato sob níveis de fertirrigação e métodos de extração da solução. - Mota, Poliana Rocha D'Almeida; Bôas, Roberto Lyra Villas [UNESP]; Ludwig, Fernanda [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Folegatti, Marcos Vinícius (Lepidus Tecnologia, 2011)
The present work was developed with the objective of evaluate the pH and electrical conductivity (EC) of substrate submitted to the fertigation with different concentrations and extraction method. The study was carried out in a greenhouse at Department of Natural Resources/Science of Soil, of the FCA/UNESP, of February to March of 2006. The experimental design were randomized blocks utilizing the plan factorial 5 x 2 (5 levels of electrical conductivity and 2 extraction method) with five repetitions. The levels of CE of the solution applied were: 0.5; 2.0; 3.5; 5.0 and 6.5 dS m-1, and the approaches: extractor of solution and pourthru. The experiment was conducted in potted with volume of 1.3 L, being the substrate constituted of the mixture of 30% of land of subsurface and 70% fine pine bark. The quantification of the EC and of the pH was carried out to the 9, 16, 23, 37, 44 and 51 days after the beginning of the application. The pH and EC were higher when the solution was extracted by the method pourthru due to the local extraction and the substrate physical characteristic. The pH and EC were higher when the solution was extracted by the pourthru due to the local extraction and the substrate physical characteristic. Was obtained coefficient of correlation between the two method of 0.96** to CE and 0.87** to pH. The conclusion was the use of the extractor of solution and the pourthru they can be utilized for evaluation of the pH and of the EC of the substrate, making feasible the management of the fertigation.

O presente trabalho foi desenvolvido com o objetivo de avaliar o valor de pH e a condutividade elétrica (CE) da solução em equilíbrio com substrato sob níveis de fertirrigação e métodos de extração da solução. O estudo foi realizado em cultivo protegido no Departamento de Recursos Naturais/Ciência do Solo, da FCA/Unesp, de fevereiro a março de 2006. Adotouse o delineamento experimental em blocos casualizados utilizando o esquema fatorial 5 x 2 (5 níveis de CE e 2 métodos de extração) com cinco repetições. A CE das soluções aplicadas foi de 0,5; 2,0; 3,5; 5,0 e 6,5 dS m-1, e os métodos foram extrator de solução e “pourthru”. O experimento foi conduzido em vaso plástico com volume de 1,3 L, sendo o substrato constituído da mistura de 30% de terra de subsuperfície e 70% casca de pinus fina. As quantificações da CE e do pH foram feitas aos 9, 16, 23, 37, 44 e 51 dias após o início das aplicações da fertirrigação. Os valores de pH e CE foram superiores quando a solução foi extraída pelo método “pourthru”, devido ao local de extração e à característica física do substrato. Obteve-se coeficiente de correlação entre os dois métodos de 0,96** para a CE e de 0,87** para o pH. Conclui-se que o uso do extrator de solução e o “pourthru” podem ser utilizados para avaliação do pH e da CE dos substratos, viabilizando o manejo da fertirrigação.
pH and electrical conductivity of substrate submitted to the fertigation with different concentrations and extraction method
Keywords: Extractor of solution; Pourthru; Nutrient management; Extrator de solução; Pourthru; Manejo de nutrientes